1990
DOI: 10.1083/jcb.110.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Chinese hamster ovary cell mutants defective in intracellular low density lipoprotein-cholesterol trafficking.

Abstract: This paper reports the isolation and characterization of Chinese hamster ovary cell mutants defective in low density lipoprotein (LDL)- cholesterol trafficking. The parental cell line was 25-RA, which possesses LDL receptors and various cholesterogenic enzyme activities that are partially resistant to down regulation by exogenous sterols (Chang, T. Y., and J. S. Limanek. 1980. J. Biol. Chem. 255:7787-7795). Because these cells accumulate a large amount of intracellular cholesteryl ester when grown in medium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…S1 A). The labeled lipids were extracted and analyzed on silver nitrate impregnated TLC plates (47); the percentage hydrolysis of 3 H-CL and the percentage re-esterification of 3 H-LDL-CHOL were calculated as described (2). To conduct the cholesterol efflux experiments, cells were incubated with 4% 2-hydroxypropyl-␤-CD in Medium D at 37°C during the last 10 min of the chase period (2).…”
Section: Methodsmentioning
confidence: 99%
“…S1 A). The labeled lipids were extracted and analyzed on silver nitrate impregnated TLC plates (47); the percentage hydrolysis of 3 H-CL and the percentage re-esterification of 3 H-LDL-CHOL were calculated as described (2). To conduct the cholesterol efflux experiments, cells were incubated with 4% 2-hydroxypropyl-␤-CD in Medium D at 37°C during the last 10 min of the chase period (2).…”
Section: Methodsmentioning
confidence: 99%
“…The CT mutant cell line is isolated as one of the cholesterol-trafficking mutants from mutagenized RA cells (9). It contains the same gain-of-function mutation in SCAP.…”
Section: Cell Linesmentioning
confidence: 99%
“…8). Chinese hamster ovary (CHO) mutants that are defective in the NPC1 protein have been isolated and characterized (9)(10)(11). We compared the cholesterol trafficking activities between the NPC1 mutants [CT43 (CT) and CT60] and their parental cell line 25RA (RA) (12,13), and showed that NPC1 also participates in the transport of PM-derived cholesterol to the ER.…”
mentioning
confidence: 99%
“…For these studies, NPC1 was transiently expressed in CT60 cells, a Chinese hamster ovary cell mutant in the same complementation class as NPC1 fibroblasts, which store LDL-cholesterol in perinuclear lysosomes (47,48). A plasmid expressing enhanced green fluorescent protein was co-transfected to identify transfected cells (34,40).…”
Section: Functional Analysismentioning
confidence: 99%